Virulence of urinary and faecal Escherichia coli in relation to serotype, haemolysis and haemagglutination. - van den Bosch, J. F. (Cambridge University Press, 1982)
The virulence of faecal and urinary Escherichia coli strains was studied in relation to serotype, haemolysin production and haemagglutination pattern. By means of an experimental mouse model E. coli strains can be divided into avirulent (I), mouse nephropathogenic (II), and generally virulent (III) strains. Virulent group II and group III strains were more often haemolytic and haemagglutinating than avirulent group I strains. Presence of K antigen could not be associated with virulence. Discriminant analysis for qualitative variables revealed that no combination of the investigated properties contributed more to a strain's virulence level than did one single property. It is concluded that other virulence factors, apart from haemolysin production in group II strains and haemagglutinins in group III strains, must be involved in the determination of a strain's virulence level. All O2, O6 and O18 ac strains tested were virulent, and by far the most O75 strains were avirulent, whereas other O groups were more variable with regard to virulence. Pyelonephritis strains were more often mannose-resistance haemagglutinating than faecal and other urinary isolates, indicating that mannose-resistant adhesins may be important in the pathogenesis of pyelonephritis.